Pengaruh pH dan Waktu Kontak Adsorpsi Rhodamin B terhadap Ekstrak Pekat Flavonoid dari Kulit Rambutan (Nephelium lappaceum) - Silvani Indriani Manalu; Sri Benti Etika (Lembaga Yasin AlSys, 2025)
Water pollution caused by industrial waste containing synthetic dyes such as Rhodamine B poses a serious threat to aquatic ecosystems and human health. One effective and cost-efficient method of treatment is the batch adsorption process, known for its operational simplicity and economic feasibility. This study aims to evaluate the potential of flavonoid extract as a biosorbent for Rhodamine B removal, and to determine the optimum pH, contact time, and adsorption capacity of the system. Flavonoid extract was selected due to its hydroxyl and carbonyl functional groups, which actively contribute to the adsorption process. The results indicate that the optimum pH is 3, with an adsorption capacity of 4.63710 mg/g, while the optimum contact time was reached at 60 minutes, achieving a maximum adsorption capacity of 21.59455 mg/g. These findings demonstrate that flavonoid extract, particularly derived from rambutan peel, has promising potential as a natural biosorbent for mitigating Rhodamine B contamination in aquatic environments.